The relationship of macular vessel density and foveal avascular zone with pulse wave velocity and central blood pressure in healthy adults: Persian cohort study - Hamid Reza Heidarzadeh; Elaheh Ebrahimi Miandehi; Nasser Shoeibi; Mohammad Reza Ansari Astaneh; Seyedeh Maryam Hosseini; Majid Abrishami; Mehrdad Motamed Shariati; Saeid Eslami; Parnian Arjmand; Mojtaba Abrishami (International Journal of Retina and Vitreous)
Abstract Background To evaluate the correlation of macular vessel density (VD) and foveal avascular zone (FAZ) parameters measured on optical coherence tomography angiography (OCTA) with systemic arterial stiffness using pulse wave velocity (PWV), pulse wave analysis, arterial age, and central blood pressure (CBP) measurements in healthy subjects. Methods In a comparative, cross-sectional, observational study, healthy adults who participated in the PERSIAN Cohort study at Mashhad University of Medical Sciences were included in this study. The study involved using a spectral domain OCTA device to obtain 3 × 3 and 6 × 6 mm scans of the macular superficial capillary plexus (SCP) VD, deep capillary plexus (DCP) VD, and FAZ vascular analysis. Additionally, we used the SphygmoCor XCEL System (AtCor, Itasca, IL) to analyze systemic vascular parameters like CBP and PWV. Results The study included 296 healthy participants with a mean age of 39.2 ± 6.7 years, and 152 subjects (51.3%) were female. Female participants were found to have higher DCP VD and FAZ area values. Age showed a negative correlation with SCP and DCP VDs. PWV showed a negative correlation with parafoveal DCP VDs, but no correlation was observed between macular VDs and aortic diastolic and systolic pressures. Conclusion In conclusion, age was found to have a negative impact on macular SCP and DCP VDs. In addition, higher arterial stiffness was found to correlate with a lower parafoveal DCP VD value. These findings suggest macular OCTA parameters may be used as early markers of systemic arterial disease.